Mechanism of action of “cistanche deserticola–Polygala” in treating Alzheimer's disease based on network pharmacology methods and molecular docking analysis - Shaoqiang Wang; Yifan Wang (IET Systems Biology)
Abstract This article used network pharmacology, molecular docking, GEO analysis, and Gene Set Enrichment Analysis to obtain 38 main chemical components and 66 corresponding targets involved in Alzheimer's disease (AD) treatment in "Cistanche deserticola‐Polygala". Through further Gene Ontology and Kyoto Encyclopaedia of Genes and Genomes enrichment analysis, we obtained AD signalling pathways, calcium signalling pathways, and other signalling pathways related to the treatment of AD with “Cistanche deserticola‐Polygala”. Molecular docking showed that most of the core chemical components had good binding ability with the core targets. This article aims to reveal the mechanism of “Cistanche deserticola‐Polygala” in treating AD and provide a basis for the treatment of AD with “Cistanche deserticola‐Polygala”.